Penataan Distribusi Air Permukaan untuk Efisiensi Penggunaan dan Pemanfaatan Air Di Desa Hamparan Perak - Yudha Hanova; Rizky Franchitika (Universitas Harapan Medan, 2021)
One of the efforts to increase the productivity of agricultural land in the Desa Lama is to manage surface water caused by excess rainwater. Arrangement of surface water on agricultural land will have a positive impact on plant growth because the water needs of plants can be fulfilled, especially in the dry season. The arrangement of the system aims to distribute surface water and rainwater evenly in agricultural areas. This study aims to analyze the arrangement of surface water on agricultural land with a catchment system as a medium for managing rainfall that falls so that farmers can utilize and distribute water to agricultural land by designing reservoirs. In the Desa Lama, Hamparan Perak District, Deli Serdang Regency. The method used in this study consists of, 1) Hydrological analysis such as analysis of maximum daily rainfall, return period rainfall, analysis of hourly rainfall distribution, and return period discharge. 2) Analysis of storage capacity. From the implementation of the design of the storage carried out in the field, it was obtained that the surface water storage capacity was 37.47 m3/s. Based on the hydrological analysis results, the storage capacity is the storage capacity for the 20 year return period.